EVALUASI PROGRAM PENGEMBANGAN KINERJA PENGELOLAAN PERSAMPAHAN DI KOTA TEGAL - Indah Fitriani; Herbasuki Nurcahyanto (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2017)
The problem of garbage in Tegal caused by inadequate waste management are also difficulties in obtaining land Landfill (TPA) and the technical operation of waste facilities and infrastructure are inadequate. Based on these issues, the Government of Tegal implement one program from the Department of Housing and Urban Spatial Tegal in waste management is a development program of performance management of waste derived from the vision and mission Diskimtaru, to measure the success of the program is carried out using a logical framework approach project (KKLP) which includes the evaluation indicators(inputs,outputs, outcomes, benefits, impact) and using theoretical models Korten conformity of the program. This study used quantitative research methods. The results showed that the performance of waste management development program got a score of 71% performance which shows that the performance of waste management development program included a category quite successful. Not to the success of the program due to an inhibiting factor in the development of the program of waste management’s performance, so one suggestion to conduct the program in the performance of waste management is completeness of infrastructures and facilities in every place integrated waste management (TPST)